The diagnosis of multiple opportunistic infections in advanced stage AIDS: when Ockham's Razor doesn't cut it - Marcos Vinicius Cardoso Pinheiro; Yeh-Li Ho; Antonio Carlos Nicodemo; Amaro Nunes Duarte-Neto (University of São Paulo, 2019)
In the advanced stage of AIDS, the diagnosis of the opportunistic infections may be challenging due to the high risk of performing invasive diagnostic methods in a patient with a critical clinical condition, as well as the correct interpretation of the results of microbiological exams. One of the challenges for the diagnosis and treatment of the opportunistic infections is that they may occur concomitantly in the same patient and they may mimic each other, leading to a high discrepancy between clinical and autopsy diagnoses. We describe the case of a 52-year-old man who was hospitalized because of weight loss, anemia, cough, and hepatosplenomegaly. During the investigation, the diagnosis of AIDS was made, and the patient developed respiratory failure and died on the fourth day of hospitalization. At autopsy, disseminated non-tuberculosis mycobacteriosis was found, affecting mainly the organs of the reticuloendothelial system. Also, severe and diffuse pneumonia caused by multiple agents (Pneumocystis jirovecii, Histoplasma capsulatum, suppurative bacterial infection, non-tuberculosis mycobacteria, and cytomegalovirus) was seen in a morphological pattern that could be called "collision pneumonia." The lesson from this case, revealed by the autopsy, is that in advanced AIDS, patients often have multiple opportunistic infections, so the principle of Ockham's razor-that a single diagnosis is most likely the best diagnosis-fails in this clinical context.